2016
DOI: 10.4314/ovj.v6i2.1
|View full text |Cite
|
Sign up to set email alerts
|

Expression, purification and immunochemical characterization of recombinant OMP28 protein of <i>Brucella</i> species

Abstract: Brucellosis is the lion's share of infectious disease of animals and it has a particular socio-economic importance for the Republic of Kazakhstan. Sixty percent of epizootic outbreaks of brucellosis identified in the Commonwealth of Independent States (CIS) originated from Kazakhstan in recent years. Definitive diagnosis of brucellosis remains a difficult task. Precisely for this reason, we evaluated a purified recombinant out membrane protein 28 (rOMP28) of Brucella species (Brucella spp.) produced in Escheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
0
12
1
1
Order By: Relevance
“…2.2), which further confirmed the antigenicity of the Omp28 protein. Earlier some researchers reported the formation of inclusion bodies in Omps expression (MANAT et al, 2016;YOUSEFI et al, 2016), but in our study we did not observe any inclusion body formation, even at a higher inducer concentration (IPTG). Omp28 protein is formed by three identical subunits which are not linked by disulfide bonds, representing a molecular mass of 28 kDa (NEVES-FERREIRA et al, 2004).…”
Section: Resultscontrasting
confidence: 83%
“…2.2), which further confirmed the antigenicity of the Omp28 protein. Earlier some researchers reported the formation of inclusion bodies in Omps expression (MANAT et al, 2016;YOUSEFI et al, 2016), but in our study we did not observe any inclusion body formation, even at a higher inducer concentration (IPTG). Omp28 protein is formed by three identical subunits which are not linked by disulfide bonds, representing a molecular mass of 28 kDa (NEVES-FERREIRA et al, 2004).…”
Section: Resultscontrasting
confidence: 83%
“…Escherichia coli BL21 strains, producing Brucella recombinant proteins, were obtained as described in our previous studies: B. abortus rOMP25 and B. melitensis rOMP31 [16], rBP26 [14], and rSOD [17].…”
Section: Microbial Culturesmentioning
confidence: 99%
“…Among the known rOMPs, the most studied ones are rOMP25 [12] and rOMP31 [13]. Another group of recombinant proteins, which is of great interest from a diagnostic point of view, are periplasmic proteins: rBP26 or rOMP28 [14] and Cu-Zn superoxide dismutases (rSOD) [15]. However, the comparative diagnostic value of these two groups of Brucella proteins is still scarcely explored.…”
Section: Introductionmentioning
confidence: 99%
“…In another study by Manat et al, (2016) a purified recombinant outer membrane protein 28 (rOMP28) of Brucella species produced in Escherichia coli (E. coli) was evaluated as a diagnostic antigen in an Indirect ELISA (I-ELISA) for bovine Brucellosis. The results showed that the rOMP28 of Brucella spp.…”
Section: Biomarkers Of Brucella and Brucellosismentioning
confidence: 99%